1999
DOI: 10.1159/000011970
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD44 Variant 6 as a Prognostic Indicator in Patients with Colorectal Cancer

Abstract: The expression of CD44v6 is well known as a useful marker of tumor progression and prognosis in colorectal cancer. In this study, we evaluated the serum levels of soluble CD44 splice variants containing exon v6 (sCD44v6) and examined the histological expression of CD44v6 in patients with colorectal cancer. Serum samples were obtained from 44 primary colorectal cancer patients before surgery. We used enzyme-linked immunosorbent assay to determine the serum levels of sCD44v6. The expression of CD44v6 was examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 25 publications
1
47
1
Order By: Relevance
“…Moreover, when the diagnostic sensitivity of sCD26 and CEA by Dukes' sCD26 as diagnostic andprognostic marker in CRC patients 1143 British Journal of Cancer (2000) 83 (9), 1139-1146 stage were compared, sCD26 presents higher sensitivity than CEA to diagnose patients in Dukes' A, B and C stages. As recently reported, serum TIMP-1 (plasma tissue inhibitor of metalloproteinase) or sCD44v6 screened better only the Dukes' stage D CRC (Holten-Andersen et al, 1999;Yamane et al, 1999), and serum YKL-40 (Cintin et al, 1999) was clearly a poorer marker of diagnosis. Our conclusion is that preoperative sCD26 level is an useful, easy to handle marker for early detection of potentially curable CRC.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Moreover, when the diagnostic sensitivity of sCD26 and CEA by Dukes' sCD26 as diagnostic andprognostic marker in CRC patients 1143 British Journal of Cancer (2000) 83 (9), 1139-1146 stage were compared, sCD26 presents higher sensitivity than CEA to diagnose patients in Dukes' A, B and C stages. As recently reported, serum TIMP-1 (plasma tissue inhibitor of metalloproteinase) or sCD44v6 screened better only the Dukes' stage D CRC (Holten-Andersen et al, 1999;Yamane et al, 1999), and serum YKL-40 (Cintin et al, 1999) was clearly a poorer marker of diagnosis. Our conclusion is that preoperative sCD26 level is an useful, easy to handle marker for early detection of potentially curable CRC.…”
Section: Discussionmentioning
confidence: 51%
“…In oral cancer patients, in which around a 50% decrease in serum DPP-IV activity has been reported, a correlation between sCD26 and CD26+ T was found, and the number of T lymphocytes and PBL and the amount of CD26 in T lymphocyte plasma membranes were significantly less than in healthy subjects (Uematsu et al, 1996;. Both possibilities can explain the donor-dependent variations, but the second one seems more probable in the cases of hemicolectomy or rectoragy (some of the lower values of the BPI group), except the Dukes' stage D cases with high sCD26 values, perhaps associated with a high proliferative (hepatic) cellular state, or with a later activation of PBL as suggested in CRC and ovarian tumours for the soluble CD44v6 glycoprotein (Sliutz et al, 1995;Yamane et al, 1999). It seems, then, necessary to collect the lymphocyte count and other immune parameters of the patients in future studies of CRC.…”
Section: Discussionmentioning
confidence: 92%
“…CD44 cleavage was achieved with a proteolytic enzyme, predominantly ADAM10/17; this enzyme cleaved the soluble extracellular epitope of CD44 to a soluble form (sCD44) (Okamoto et al 2002;Stamenkovic and Yu 2009). It has been reported that sCD44 (CD44-v6 or CD44-v5) could be of an independent prognostic value in colorectal and breast cancer patients (Kittl et al 1997;Yamane et al 1999;Amirghofran et al 2008). In head and neck cancer, Franzmann et al (2007) found that sCD44 was elevated in oral rinses of the majority of HNSCCs and could be highly distinguished cancer from benign disease.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12]. However, particularly in colorectal cancer, contradictory findings have been reported that range from a positive to an inverse correlation between CD44v6 expression and prognosis in colorectal cancer (13)(14)(15)(16)(17)(18)(19)(20). The same conflicting data were found for expression of CD44s (CD44 standard isoforms; refs.…”
Section: Introductionmentioning
confidence: 99%